Effects of ultra-high dilutions of sodium butyrate on viability and gene expression in HEK 293 cells. Issue 1 (February 2017) - Olsen, Steven
Abstract : Background: Several recent studies reported the capability of high diluted homeopathic medicines to modulate gene expression in cell cultures. In line with these studies, we examined whether ultra-high dilutions (30C and 200C) of sodium butyrate (SB) can affect the expression levels of genes involved in acquisition of a senescence-associated secretory phenotype (SASP) in human embryonic kidney (HEK) 293 cells. Methods: Cell viability was evaluated using a 3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide (MTT) assay. The expression levels of TNF-α, interleukin (IL)-2, IL-4, IL-6 and IL-10 genes were determined by real-time PCR assay. Results: Exposure to both 30C and 200C during 48 h led to a significant decrease of the level of expression of TNF-α gene, while expression of IL-2 gene was increased when exposed to 30C, and expression of IL-10 gene was decreased when exposed to 200C. No changes in expression levels of all genes studied were observed in cells treated with both 30C and 200C remedies of SB during the 24 h. Conclusion: Observed changes in gene expression levels after exposure to 30C and 200C remedies of SB during 48 h suggest that extremely low concentrations of this agent can modulate the transcriptome of HEK 293 cells. These results are in line with findings from other studies confirming the ability of homeopathic remedies to modulate gene expression in cell cultures. Highlights: 30C and 200C of sodium butyrate did not change the death rate of HEK 293 cells. These remedies changed expression of TNF-α, IL-2 and IL-10 genes in this cell culture. Homeopathic remedies can modulate the transcriptome of cultured cells.